METHODS OF ORIENTING STUDENTS TOWARDS A PROFESSION IN THE PROCESS OF ORGANIZING LABOR TRAINING (TAMADDUN NURI JURNALI, 2025)
The main purpose of professional orientation of young people is to prepare the younger generation for independent career choice, to teach awareness of their interests and abilities. This article will focus on the problems that arise in determining the professional interests of young people, ensuring educational continuity in their professional orientation and career choice.